Proceedings of the SmartCity360 2016 2017
DOI: 10.4108/eai.14-2-2017.152553
|View full text |Cite
|
Sign up to set email alerts
|

A probability based hybrid energy-efficient privacy preserving scheme to encounter with wireless traffic snooping in smart home

Abstract: Application of pervasive computing devices in smart homes are rising sharply and due to this matter, demands for efficient privacy protection are increasing urgently. Possibility of interference in wireless networks is proved by previous work. Adversaries can discover contextual information because of traffic monitoring and classifying transmitters based on their radio fingerprints while data packets are encrypted or content is not important for attackers. To conceal communication patterns various approaches h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Both of these mistakes affect the correctness rate of the attack. Figure 8 illustrates a schematic view of the network traffic in which the attack has formed six activity frames; frames 1 and 5 are correct detections, frame 6 is a false positive, and frames 2 and 3 are undetected events by the attack [ 54 , 55 , 56 ].…”
Section: Privacy Protection Strategies Against the Fats Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these mistakes affect the correctness rate of the attack. Figure 8 illustrates a schematic view of the network traffic in which the attack has formed six activity frames; frames 1 and 5 are correct detections, frame 6 is a false positive, and frames 2 and 3 are undetected events by the attack [ 54 , 55 , 56 ].…”
Section: Privacy Protection Strategies Against the Fats Attackmentioning
confidence: 99%
“…The authors in [ 56 ] briefly introduced a novel concept to counter FATS attacks and suggested a paradigm-shifting strategy for injecting fake packets. The proposed notion is to inject dummy packets collaboratively to impersonate an actual in-home activity; thus, even though these random injections do not interfere with an actual pattern, they can deceive the attack by themselves and prevent energy wastage.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, each action in the home is exposed to attackers. [46] introduced this attack, and [47], [48] have shown potential solutions to this attack.…”
Section: Infrastructure Layermentioning
confidence: 99%